Implementasi Flex Sensor Dan Wireless Module Sebagai Alat Bantu Pasien Afasia Motorik - Halifia Hendri; Harkamsyah Andrianof; Okta Andrica Putra; Hasri Awal; Dendi Novrizal (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
In the era of technology developing rapidly as it is today, of course, there are many new things being done by the health sector. As a form of convenience in the health sector. With that, the health sector utilizes and applies and develops existing technology as a tool to facilitate and support new adaptations. One of them is by implementing a motor aphasia patient communication system that utilizes the basics of hand kinematics with nurses. This study was conducted aimed at motor aphasia patients and nurses in the health sector. The system is used as a communication tool between motor aphasia patients and nurses. The tool is equipped with a sensor flex as input expenditure command aphasia patient motor by utilizing the basic kinematics of the hand which will then be sent via wireless to the hardware nurse who later dihardware nurses as the output will be sounding the command through the speakers is detected by the sensor flex